2005
DOI: 10.1007/s10778-006-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary waves in an inelastic disk under impulsive radial loading

Abstract: Nonstationary axisymetric waves in a disk excited by an impulsive radial load are analyzed numerically. The nonlinear deformation of the material is described by the Bodner-Partom model. The model parameters are derived from experimental data for samples subjected to tension followed by compression over a wide range of strain rates. The temporal and spatial characteristics of the wave process are studied. The influence of hardening on wave focusing and residual strain distribution is examined Keywords: nonstat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Experimental and theoretical studies of their dynamic characteristics are reported in numerous scientific publications, which are mainly focused on stationary harmonic vibrations and resonant frequencies [1, 2, 9, 13, 14, etc.]. Aspects of the nonstationary vibrations of circular disks were analyzed in [3,11] regardless of the coupling of the fields. The vibrations of piezoceramic bodies polarized across the thickness and subjected to nonstationary loads were studied in [6,7,10,12], naturally neglecting the influence of the in-plane configuration of transducers on the wave processes.…”
mentioning
confidence: 99%
“…Experimental and theoretical studies of their dynamic characteristics are reported in numerous scientific publications, which are mainly focused on stationary harmonic vibrations and resonant frequencies [1, 2, 9, 13, 14, etc.]. Aspects of the nonstationary vibrations of circular disks were analyzed in [3,11] regardless of the coupling of the fields. The vibrations of piezoceramic bodies polarized across the thickness and subjected to nonstationary loads were studied in [6,7,10,12], naturally neglecting the influence of the in-plane configuration of transducers on the wave processes.…”
mentioning
confidence: 99%
“…One of the most significant criteria that a complex model is adequate and correct is its consistency with the simpler models generalized by it. In our case, this means that the constitutive equations describing elastic deformation, viscous flow, and plastic deformation should follow, as partial or limiting cases, from the constitutive equations of viscoelastoplasticity.Recently, the theory and problems of viscoelastoplasticity have widely used the Bodner-Partom model [7,8,[12][13][14][15][20][21][22][23], which, along with stresses and strains, uses internal variables describing isotropic and kinematic hardening for which evolutionary equations are formulated. In this model, strains have elastic and inelastic components, and inelastic strain rates are specified as a negative exponential function of the ratio of the sum of hardening parameters to stresses.…”
mentioning
confidence: 99%
“…(1.4) and (1.9) by the mesh-interpolation method. Nowadays, the finite-element method is widely used to set up finite-difference equations [12,15,16].…”
mentioning
confidence: 99%